Gene profiling reveals the role of inflammation, abnormal uterine muscle contraction and vascularity in recurrent implantation failure - Dong, Xinyi; Zhou, Mi; Li, Xinyu; Huang, Huijing; Sun, Yun (Frontiers in Genetics, 2023)
Objective: Recurrent implantation failure (RIF) is now disturbing numerous infertile couples accepting assisted reproductive technology (ART). And the endometrial factors are crucial causes of RIF. However, its mechanism is still unclear. Thus, the aim of this study is to identify altered biologic processes in endometrium that may contribute to RIF. Methods: We recruited 2 microarray datasets (GSE103465, GSE111974) from Gene Expression Omnibus database (GEO), which contain endometrium from RIF and normal women during implantation period. Using the online tools GEO2R and Venny, we identified differentially expression genes (DEGs) of selected datasets, and obtained common DEGs. Gene Ontology (GO) terms, Kyoto Encyclopedia of Genes and Genomes (KEGG) and BioCatar pathway enrichment were conducted with Enrichr platform, “ssgsea” and “ggplot2” package of RStudio. PPI networks and hub gene related TF-gene interaction and TF-miRNA co-regulation networks were built via online tools STRING and NetworkAnalyst. Immune infiltration analysis was performed by CIBERSORT platform. RIF subgroup identification was achieved through “ConsensusClusterPlus”, “tsne”, “ssgsea” and “ggpubr” package in RStudio. Diagnostic characteristic ROC curves were constructed via “pROC” and “ggplot2” package of RStudio. Enrichr platform was utilized to find drugs targeting hub genes. Results: 26 common DEGs were confirmed. GO and KEGG/BioCarta analysis determined common DEGs were mainly enriched in inflammation associated pathways including TNF, NF-κB, IL-4, IL-10, IL-6 and TGF-β signaling pathways. 5 hub genes (PTGS2, VCAM1, EDNRB, ACTA2 and LIF) and related TF-gene and TF-miRNA interactions were identified. Immune infiltration analysis indicated the importance of macrophage M2 in RIF patients. Importantly, subgroup identification analysis highlighted that RIF patients can be divided into two subgroups with different phenotypes. Moreover, the ROC curves and drugs may provide new diagnostic and therapeutic thought for RIF.